Review of Joanna Innes and Mark Philp, eds., Re-imagining Democracy in the Mediterranean, 1780–1860 - Zanou, Konstantina (Historein, 2022)
Review of Joanna Innes and Mark Philp, eds., Re-imagining Democracy in the Mediterranean, 1780–1860. Oxford: Oxford University Press, 2018. xvi + 337 pp. To view the full text, click on the button "HTML".